2020
DOI: 10.3390/w12030618
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Salinity on the Growth of Lavender Species

Abstract: Long term degradation of water quality from natural resources has led to the use of alternative water resources for irrigation that are saline. Saline water irrigation in floriculture for the production of nursery crops requires an understanding of plant response. The pot growth of four lavender species (Lavandula angustifolia, Lavandula dentata var. dentata, Lavandula dentata var. candicans and Lavandula stoechas) irrigated with water containing different concentrations of NaCl (0, 25, 50, 100 and 200 mM) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The remarkable reduction of morphological characteristics of P. amboinicus are attributed to different levels of salt in irrigation water. Such consequences have been observed in several plant species including Plectranthus forsteri (Krzymińska and Ulczycka-Walorska, 2015 ), P. amboinicus (Karimian et al, 2019 ), and lavender ( Salvia splendens ) (Paraskevopoulou et al, 2020 ). On the other hand, significant increases in the abovementioned growth parameters of P. amboinicus compared with the control (spray with water) were observed when FA was applied as a foliar spray at concentrations of 25 or 50 μM.…”
Section: Discussionmentioning
confidence: 98%
“…The remarkable reduction of morphological characteristics of P. amboinicus are attributed to different levels of salt in irrigation water. Such consequences have been observed in several plant species including Plectranthus forsteri (Krzymińska and Ulczycka-Walorska, 2015 ), P. amboinicus (Karimian et al, 2019 ), and lavender ( Salvia splendens ) (Paraskevopoulou et al, 2020 ). On the other hand, significant increases in the abovementioned growth parameters of P. amboinicus compared with the control (spray with water) were observed when FA was applied as a foliar spray at concentrations of 25 or 50 μM.…”
Section: Discussionmentioning
confidence: 98%
“…In the current study, we evaluated the effects of salinity stress on some physiological characteristics of lavender in the presence/ absence of nanoparticle treatment. Previous investigations (García-Caparrós et al, 2016: Paraskevopoulou et al, 2020 revealed that NaCl concentrations greater than 60 mM affect plant growth and development in lavender species. However, in some Lavandula species, salinity concentrations of 100 mM and 200 mM decreased plant biomass (Plaza et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…candicans, L. multifida, L. stoechas, and L. angustifolia. The results of these evaluations showed that specific concentrations of salinity stress can affect growth and development of lavender plants (Plaza et al, 2015;García-Caparrós et al, 2016: Paraskevopoulou et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Seed germination and early seedling growth, being the most fragile and vulnerable phases in plant life cycle, are intimately connected and closely effected by various overlapping environmental factors such as temperature, water availability, soil salinity and light, thereby seedling establishment requirements are the bottleneck that should be framed, whether for the crop production or land restoration (Zhang et al, 2018;Paraskevopoulou et al, 2020). For example, soil salinity could disturb directly plant plasticity via the harmful effects of excessive ion accumulation (i.e.…”
Section: Salt and Drought Effect On Germination And Initial Growth Of...mentioning
confidence: 99%
“…Lavender is distributed over North Africa, the Mediterranean basin, Europe and western India. This species is found naturally growing in the coastal shrub lands, coastal garrigues and sea cliffs, often exposed to sea spray (Paraskevopoulou et al, 2020). It is commercially cultivated worldwide in a number of countries mainly in Europe and Asia (Shawl, Kumar, 2000;Lawrence, 2008).…”
Section: Salt and Drought Effect On Germination And Initial Growth Of...mentioning
confidence: 99%